Experimental and numerical investigation of low‐cycle fatigue behavior of 9Cr ferritic‐martensitic steel at room temperature. Issue 2 (21st January 2020) - Zhang, Zhen; Tu, Haoyun; Hu, Zhengfei; Li, Yan; Zhang, Baosen; Wang, Zhangzhong
Abstract: The low‐cycle fatigue (LCF) behavior of 9Cr ferritic‐martensitic steel has been investigated over a range of controlled total strain amplitudes from 0.25 to 0.8% at room temperature (RT). The LCF properties of P92 steel at RT follow Coffin‐Manson relationship. Cyclic stress response of the P92 steel at RT contains three stages, in which the rapid softening and saturation part of cyclic softening stage can be described by the nonlinear isotropic/kinematic hardening model, and the softening rate and strength are enhanced with the increase of strain amplitudes. The influence of strain amplitude on the fatigue crack growth has been studied by using a scanning electron microscope, and it shows that the number of fatigue sources and secondary cracks increase with the increase of strain amplitudes.